Promoting entrepreneurial orientation through the accumulation of social capital, and knowledge management. (April 2015) - Liu, Chih-Hsing; Lee, Tingko
Abstract: Management scholars and tourism practitioners emphasize the importance of knowledge management to and social capital of medium and small vendors' entrepreneurial orientation. Constraints on medium and small vendors' time and energy suggest that accumulating social capital is helpful to enhance knowledge management. Furthermore, how and why medium and small networks contribute to entrepreneurial orientation deserves further investigation. In this study, we offer hypotheses to shed insight on the interrelationships among critical attributes of social capital and further test the mediation role of knowledge management that may contribute to entrepreneurial orientation between medium and small vendors. We tested our hypotheses using data collected from 286 medium and small vendors in night markets located in different regions of Taiwan. Study findings identified different relationships among social capital, confirming our hypothesis that social capital affects knowledge management and its application. We further demonstrate that social capital and entrepreneurial orientation are fully mediated by knowledge management. Implications for future research on tourism industry management and medium and small firms' managers are discussed.